A longitudinal comparison of customer satisfaction and customer-company identification in a service context. Issue 5 (17th October 2016) - Huang, Min-Hsin; Cheng, Zhao-Hong
Abstract : Purpose: Customer satisfaction (CS) and customer-company identification (CCI) are two important relational constructs and play a complementary role in the service-profit chain. Drawing from the theory of relationship dynamics, the purpose of this paper is to define CS velocity and CCI velocity as the rate and direction of change in CS and CCI, respectively. A comparison of the relative effects of CCI velocity and CS velocity on customer loyalty is done through a latent growth curve modeling approach. Design/methodology/approach: A conceptual model is developed and empirically tested based on four waves of a longitudinal survey of 213 restaurant customers. Findings: The results show that both CCI velocity and CS velocity have positive effects on customer loyalty. More importantly, the effects of CCI velocity on customer loyalty over time are stronger than those of CS velocity. The moderation analysis further shows that the higher the frequency of visits to the service firm, the stronger the effects of relationship velocity on customer loyalty. Practical implications: The results provide new insights for service marketing managers by suggesting that, to benefit the long-term effectiveness of relationship investments, service firms should shift the priority from increasing CS to engendering CCI. Originality/value: This paper contributes to the theory of relationship dynamics by conceptualizing new constructs of CS velocity and CCI velocity and by empirically comparing their relative effects on customer loyalty over time.